Cleaning ECG with Deep Learning - Dias, Mariana (2024)
Funding Information: Open access funding provided by FCT|FCCN (b-on). This work was supported by Project OPERATOR (NORTE01-0247-FEDER-045910), cofinanced by the European Regional Development Fund through the North Portugal Regional Operational Program and Lisbon Regional Operational Program and by the Portuguese Foundation for Science and Technology, under the MIT Portugal Program. Publisher Copyright: © The Author(s) 2024.